Catalytic conversion of spent frying oil into biodiesel over raw and 12-tungsto-phosphoric acid modified clay. (August 2020) - Khan, Ihtisham Wali; Naeem, Abdul; Farooq, Muhammad; Mahmood, Tahira; Ahmad, Bashir; Hamayun, Muhammad; Ahmad, Zahoor; Saeed, Tooba
Abstract: In the present work, locally available clay has been utilized to develop cost effective catalyst for biodiesel production from low cost feedstock. The selected clay was modified with different concentrations (5 wt%, 10 wt%, 20 wt%, 30 wt% and 40 wt %) of 12-tungstophosphoric acid (TPA) to enhance the capability of the selected clay in biodiesel production from spent frying oil. The synthesized catalyst was characterized with different analytical techniques to evaluate its physiochemical properties. The result suggested that the catalyst containing 10 wt% 12-tungstophosphoric acid (TPA) loading exhibited good trans-esterification activity to produce maximum biodiesel yield of 96% under the best reaction conditions: oil/methanol molar ratio, 1:10; catalyst amount, 0.7 g; reaction time, 4.5 h and reaction temperature, 85 °C. Moreover, the catalytic reusability of the synthesized catalyst was investigated to study its economic viability. The results suggested that the synthesized catalyst could be reused up to 6 times for biodiesel production without any high temperature treatment. Thus, the selected clay has the potential to be used as a starting material to develop an efficient catalyst for biodiesel production from low cost feedstock. Graphical abstract: Image 1 Highlights: TPA modified bentonite clay was used as an efficient catalyst for the conversion of spent frying oil into biodiesel. TPA significantly improves the catalytic activity of the bentonite clay. TPA modified bentonite clay showed 96% yield of FAME under mild reaction condition. The synthesized catalyst was reused upto six successive run.